The Toys Party - Hunt,Roderick (China : Oxford university press., 2012)
The Oxford Reading Tree reader "The Toys' Party" is part of the Biff, Chip, and Kipper series within Oxford Reading Tree. This series is designed for young learners and focuses on developing reading skills through engaging stories featuring the characters Biff, Chip, and Kipper. The "Toys' Party" book is specifically at Level 2.
Keywords: English - Oxford Reading Tree